DEINDUSTRIALIZATION AS A PROCESS IN THE EU - Vinko Kandžija; Marko Tomljanović; Ivona Huđek (Ekonomski Vjesnik, 2017)
Deindustrialization is a natural process in the developed countries, which takes place under the influence of external and internal factors and occurs as a result of economic growth. It is marked by the decline in the share of industry in GDP and employment with a simultaneous increased importance of the service sector. Considering the complexity of the concept, there are many theoretical approaches of deindustrialisation. In this paper the analysis of deindustrialization in the EU was conducted. The research results indicate the existence of relative deindustrialization in the EU, which is characterized by reduced share of agriculture and industry and increased share of the service sector in GDP. Also, it was found that the decrease in employment in the industry was not created as a result of a decrease in industrial production. The EU economy, including the industrial sector, is heavily influenced by the globalization process, while the process of deindustrialization is significantly impacted by the increased volume of foreign direct investment. In key strategic documents European industry is recognized as the main "engine" of the recovery of the European economy. Therefore, the highest  priority is the creation of conditions for the process of reindustrialization, i.e. the development of industry in the variable circumstances, with an emphasis on strengthening and improving the industrial foundation and implementation of new solutions based on innovation, research and new technologies.